2010
DOI: 10.3152/146155110x488826
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Environmental Impact Assessment: Finnish EISs and the opinions of EIA professionals

Abstract: This article presents and compares findings of two EIA quality studies conducted in Finland. First a survey was targeted at competent authorities and environmental consultants to investigate their perceptions of the quality of Finnish EIAs. Second, 15 EISs were considered using the European Commission's guidance on review criteria. The results show that the EIA professionals generally consider the quality as good, though they also recognized that the quality varies and suggested certain areas for improvement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 21 publications
2
10
0
8
Order By: Relevance
“…These findings are broadly in line with previous studies conducted in developing countries and elsewhere (for example, Jalava et al, 2010;Sandham and Pretorius, 2008). The findings in Chapter 4 show that the quality of EISs in Bangladesh in general can be classified as being merely satisfactory, while a significant number (34%) of them are unsatisfactory.…”
Section: The Quality Of Eisssupporting
confidence: 89%
“…These findings are broadly in line with previous studies conducted in developing countries and elsewhere (for example, Jalava et al, 2010;Sandham and Pretorius, 2008). The findings in Chapter 4 show that the quality of EISs in Bangladesh in general can be classified as being merely satisfactory, while a significant number (34%) of them are unsatisfactory.…”
Section: The Quality Of Eisssupporting
confidence: 89%
“…Similar observations were made by Gray and Edward-Jones (2003), Paliwal (2006), Martin (2007), Sandham and Pretorius (2008) and Jalava et al (2010).…”
Section: Details Drugs Cement Highway Oilsupporting
confidence: 87%
“…In the Finnish context, Hildén and Jalonen (2005) report limited influence of EA on decision-making and development choices, and Pölönen (2006) concludes that both the EU Directive and the Finnish EA legislation fail to guarantee the successful transfer of assessment results to decision making. Hokkanen (2001) reports that a significant amount of raw information is generated through Finnish EA, but there is insufficient time to use the resulting knowledge; and Jalava et al (2010) report that Finnish EAs suffer from irrelevant information reported in a lengthy way, which may serve to confuse and obscure essential points.…”
Section: Impact and Influencementioning
confidence: 99%